Synergisticin vitroactivity between aztreonam and amoxicillin‐clavulanate against Enterobacteriaceae‐producing class B and/or class D carbapenemases with or without extended‐spectrumβ‐lactamases. Issue 9 (September 2019) - Ract, Pauline; Compain, Fabrice; Robin, Frédéric; Decre, Dominique; Gallah, Salah; Podglajen, Isabelle
N/A: Introduction. : Carbapenemase‐producing Enterobacteriaceae have become a major public health concern over the last decade and treatment options are limited. Aims. : We evaluated the synergistic activity of the combination of aztreonam (ATM) and clavulanate for 41 β ‐lactam‐resistant clinical isolates harbouring class B or/and class D carbapenemases combined or not with extended‐spectrum β ‐lactamases (ESBLs). Methodology. : The MICs of ATM, with and without amoxicillin‐clavulanate (AMC), were determined. Time‐kill assays were performed for three representative strains. Results. : The ATM‐AMC combination had a synergistic effect on 34/41 (83%) isolates. The MIC of ATM, in the presence of clavulanate, was ≤1 mg l −1 for 15/41 (37%) isolates and ≤4 mg l −1 for 29/41 (71%) isolates. Synergistic activity was observed for 34/37 (92%) isolates producing ESBLs and carbapenemases, compared to 0/4 (0%) for ESBL‐negative strains. Complete or partial bactericidal activity was obtained when the MIC of the combination was 0.5 mg l −1 and 1.5 mg l −1 or 8 mg l −1, respectively. Conclusion. : The combination of ATM and AMC could be an attractive unconventional treatment for infections due to carbapenemase‐ and ESBL‐producing Enterobacteriaceae.